Field theory approaches to new media practices: An introduction and some theoretical considerations - Willig, Ida; Waltorp, Karen; Hartley, Jannie Møller (MedieKultur: Journal of media and communication research, 2015)
In this article introducing the theme of the special issue we argue that studies of new media practices might benefit from especially Pierre Bourdieu’s research on cultural production. We introduce some of the literature, which deals with the use of digital media, and which have taken steps to develop field theory in this context. Secondly, we present the four thematic articles in this issue and the articles outside the theme, which includes two translations of classic texts within communication and media research. This introduction article concludes by encouraging media scholars to embark on more studies within a field theory framework, as the ability of the comprehensive theoretical work and the ideas of a reflexive sociology is able to trigger the good questions, more than it claims to offer a complete and self-sufficient sociology of media and inherent here also new media.